„Beste Landpartie Allgemeinmedizin“ (BeLA) – ein didaktisches Konzept gegen den Hausärztemangel auf dem Land - Herzog, Therese; Brandhuber, Tom; Barth, Niklas; Wijnen-Meijer, Marjo; Roos, Marco; Berberat, Pascal; Schneider, Antonius (Zeitschrift für Allgemeinmedizin, 2019)
There is a new education program for medical students (BeLA – Beste Landpartie Allgemeinmedizin), established by the Institute of Family Medicine and Health Services Research of the Technical University Munich and supported financially by the Bavarian Ministry of Health, which aims to reduce the shortage of doctors in rural areas. Participating students are supported financially and didactically from an early stage of their currricu-lum on and are bound in one of the participating regions Dillingen an der Donau, Eichstätt/Kösching and Mühldorf am Inn. The following report presents the didactical concept, general framework and goals of the promotion program.
CRIS-Team Scopus Importer:2019-11-01
Keywords: Didactical concept; Family medicine; Financial support; Lack of family physicians in rural areas